Розробка та впровадження інформаційної системи ігрового казино в сервер гри GTA - Мошенський, К. О. (ХНУРЕ, 2024)
The topic of the work is development and implementation of the information system of a gaming casino on the GTA server. The choice is due to the relevance and popularity of online casinos in the modern world, as well as the large number of players in the GTA online game. This resource differs from its competitors in that users will have the opportunity to play with play money without spending real money. There are different tables, as well as different denominations of chips. At any time, user can exchange chips for gaming funds.
Keywords: інтерфейс користувача; база даних гравців; система ставок; управління іграми; інтеграція з сервером; GTA server